Corpo e formação: uma pesquisa encarnada em terapia ocupacional - Shiramizo, Carolina da Silva (2023)
To think about the body is to contemplate the forms of life and processes of individuation that single out and give rise to different ways of thinking, acting, and living. Among the various perspectives on the body and corporeality that are emerging for/in occupational therapy in dialogue with philosophy, sociology, arts, aesthetics, culture, and movement studies, I delve into the multiple senses of the body in the formative process. From a sensitive-critical-ethical-aesthetic-political dimension, I pay attention to sensitive and singular, distinct and plural events of existence that escape the realms of hegemonic rationality based on biomedical knowledge, in order to engage with knowledge and practices that evoke sensitive shifts. The research aimed to map how themes and experiences related to the body/corporeality promote sensitive displacements in the training of occupational therapists. Using cartography as the theoretical and methodological framework, I conducted research by observing formative processes in occupational therapy in Brazil, approaching practices and themes related to the body and corporeality. The research path became embodied and has been supported by my own experience and the experiences of other occupational therapists, forming a complex web that is woven and unwoven in the encounter between our individual practices. We inhabit and explore this realm as embodied beings, seeking to apprehend the presence of other bodies and the implications of such encounters in the construction of an embodied occupational therapy. As results, I present dimensions of the teaching-learning process that emerge from the embodied experiences of the research participants, giving rise to what I have termed the "invisible curriculum." I explore the desires and commitments that influence the creation of these curricula, as well as the inventive devices that are developed as strategies in this process. Subsequently, I embrace the formative process as an act of caring for oneself and others, reaffirming the significance of bodily experiences in shaping learning and understanding its resonances. Finally, constructing the research process involves looking at what is in the flesh and acknowledging that much has been said, yet much remains to be said. I was able to delve into the plane of experience and inhabit places that, despite being unfamiliar, provided crucial insights into occupational therapy training and enabled the production of this dissertation, which surpasses the rigid dichotomies, hierarchical structures, and colonized aspects of formative processes.